Deformation of wood in compression due to moisture content changes - Chew, Meng Yew (Universiti Malaysia Sarawak, UNIMAS, 2006)
The purpose of this work is to show the magnitude of mechanosorptive creep compared to ordinary viscoelastic creep when applied compressive load. In order to do this, several conditions are induced. They are the moisture movement with moisture content (MC) change, moisture movement without MC change and conditions without moisture movement.